Alisher Navoi on justice - E. Boratov (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
In the article, the author tried to provide interpretation about the great Uzbek thinker and poet Alisher Navoi’s efforts to restore justice during his career, called the kings and officials of his time, and the people to share justice.